2006
DOI: 10.1128/jvi.80.3.1067-1076.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role and Mechanism of Action of the APOBEC3 Family of Antiretroviral Resistance Factors

Abstract: Metazoan organisms are subject to invasion by a wide range of microbial pathogens and have, as a result, evolved a range of defensive measures. While scientific attention historically has focused on adaptive immune responses, such as antibodies and cytotoxic T cells, it has of late become increasingly apparent that innate immunity also plays a key role in shielding animals from infection (62). Unlike adaptive immunity, innate immunity acts immediately and thus can prevent an infection from getting started. Inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
264
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(268 citation statements)
references
References 79 publications
(172 reference statements)
2
264
0
2
Order By: Relevance
“…Some retroviruses, such as HIV, simian immunodeficiency virus (SIV), and feline immunodeficiency virus (FIV), encode Vif proteins that bind APOBEC3 proteins and target them for degradation in virus-producing cells. Additionally, the Bet protein of feline foamy viruses inhibits APOBEC3 by as yet undetermined means (16) and human T-cell leukemia virus I prevents packaging of APOBEC3G, although not APOBEC3A, 3B, or 3H (47,48). However, APOBEC3 inhibits infection by a number of viruses that encode no apparent vif-or bet-like genes, and how these viruses overcome restriction is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some retroviruses, such as HIV, simian immunodeficiency virus (SIV), and feline immunodeficiency virus (FIV), encode Vif proteins that bind APOBEC3 proteins and target them for degradation in virus-producing cells. Additionally, the Bet protein of feline foamy viruses inhibits APOBEC3 by as yet undetermined means (16) and human T-cell leukemia virus I prevents packaging of APOBEC3G, although not APOBEC3A, 3B, or 3H (47,48). However, APOBEC3 inhibits infection by a number of viruses that encode no apparent vif-or bet-like genes, and how these viruses overcome restriction is not known.…”
Section: Discussionmentioning
confidence: 99%
“…APOBEC3 genes belong to a family of genes that encode DNA and RNA editing enzymes (16). The human genome contains seven genes, whereas mice have only one gene (17).…”
mentioning
confidence: 99%
“…The low conservation class ( Figure 3D) comprised of genes having orthologs in less than 50% of the species. Genes in this group included DCD-an antimicrobial peptide coding gene, member of the APOBEC family which are specific to primates and mammals [54]. Furthermore, nLRP11 -a member of the Nod-like receptor protein family was observed to be present only in mammals [55].…”
Section: Rbps Are Highly Conserved Across Speciesmentioning
confidence: 99%
“…The ability of human APOBEC3G (A3G) to function as an innate inhibitor of exogenous retroviruses was first noted during studies analyzing the HIV type 1 (HIV-1) Vif protein (6,13). These experiments revealed that A3G is a potent inhibitor of Vif-deficient, but not wild-type, HIV-1 replication.…”
mentioning
confidence: 99%
“…Humans are subject to infection by a limited number of exogenous retroviruses and contain few, if any, biologically active LTR retrotransposons, although a small number of structurally similar endogenous retroviruses may remain viable (5,6). However, humans contain Ϸ100 intact LINE-1 elements (7,8), and de novo LINE-1 and short interspersed element retrotransposition events occur in Ϸ10% of human genomes per generation (9,10).…”
mentioning
confidence: 99%